A 112 Gb/s Radiation-Hardened Mid-Board Optical Transceiver in 130-nm SiGe BiCMOS for Intra-Satellite Links - Giannakopoulos, Stavros; Sourikopoulos, Ilias; Stampoulidis, Leontios; Ostrovskyy, Pylyp; Teply, Florian; Tittelbach-Helmrich, K.; Panic, Goran; Fischer, Gunter; Grabowski, Alexander; Zirath, Herbert; Ayzac, Philippe; Venet, Norbert; et al. (Frontiers in Physics, 2021)
We report the design of 112 Gb/s radiation-hard (RH) optical transceiver applicable to intra-satellite optical interconnects. The transceiver chipset comprises of VCSEL driver and transimpedance amplifier (TIA) ICs integrated with four channels per die, which are adapted for flip-chip assembly into a mid-board optics (MBO) optical transceiver module. The ICs are designed in the IHP 130nm SiGe BiCMOS process (SG13RH) leveraging proven robustness in radiation environments and high-speed performance featuring bipolar transistors (HBTs) with fT/ fMAX values of up to 250/340 GHz. Besides hardening-by-technology, radiation-hardened-by-design (RHBD) components are used, including enclosed layout transistors (ELT) and digital logic cells. We report design features of the ICs and module and provide performance data from post-layout simulations. We present radiation evaluation data on the analogue devices and digital cells, which indicate that the transceiver ICs would operate under typical total ionizing dose (TID) levels and single event latch-up thresholds found in geostationary satellites.